Antimicrobial Activity and pH of Calcium Hydroxide and Zinc Oxide Nanoparticles Intracanal Medication and Association with Chlorhexidine - Aguiar, Alana Souza; Guerreiro-Tanomaru, Juliane M.; Faria, Gisele; Leonardo, Renato Toledo; Tanomaru-Filho, Mario (Jaypee Brothers Medical Publishing, 2015)
AIM: To evaluate pH and antibacterial activity of pastes with calcium hydroxide [Ca(OH)2] and zinc oxide (ZnO) microparticles (micro) or nanoparticles (nano) and association with 0.4% chlorhexidine against Enterococcus faecalis. MATERIALS AND METHODS: The following pastes were analyzed: Ca(OH)2/ZnO micro, (2) Ca(OH)2/ZnO nano, (3) Ca(OH)2/ ZnO micro + 0.4% chlorhexidine, (4) Ca(OH)2/ZnO nano + 0.4% chlorhexidine. Antibacterial activity against E. faecalis was evaluated by agar diffusion test. The direct contact test on planktonic cells of E. faecalis was performed for 30 and 60 seconds. Root canals from bovine teeth were filled with the pastes and pH was evaluated after 1, 7, 14, 21, 30 and 60 days. The data obtained were submitted to the statistical tests analysis of variance (ANOVA) and Tukey or Kruskal-Wallis and Dunn test, with a 5% significance level. RESULTS: Calcium hydroxide and zinc oxide nano, and the pastes with 0.4% chlorhexidine were more effective in agar diffusion test. In the direct contact test, the pastes with chlorhexidine showed the highest effect after 30 seconds. All pastes eliminated E. faecalis after 60 seconds. All pastes promoted an increase in pH. The highest increase in pH was observed with nanoparticle medications after 1 and 7 days (p < 0.05). After this period, the pastes presented similar pH increase. CONCLUSION: It was concluded that calcium hydroxide and zinc oxide nanoparticles promoted greater initial alkalinization. The antimicrobial activity of the pastes against E. faecalis is favored by the association with chlorhexidine. CLINICAL SIGNIFICANCE: Although nanoparticles of calcium hydroxide and zinc oxide promoted antibacterial effect, the activity against E. faecalis is favored by association with chlorhexidine.
Keywords: Antibacterial; Calcium hydroxide; Chlorhexidine; Nanoparticles; pH; Zinc oxide